Comorbid seizure reduction after pallidothalamic tractotomy for movement disorders: Revival of Jinnai’s Forel‐H‐tomy - Horisawa, Shiro (Epilepsia Open, 2021)
Forel‐H‐tomy for intractable epilepsy was introduced by Dennosuke Jinnai in the 1960s. Recently, Forel‐H‐tomy was renamed to “pallidothalamic tractotomy” and revived for the treatment of Parkinson's disease and dystonia. Two of our patients with movement disorders and comorbid epilepsy experienced significant seizure reduction after pallidothalamic tractotomy, demonstrating the efficacy of this method. The first was a 29‐year‐old woman who had temporal lobe epilepsy with focal impaired awareness seizure once every three months and an aura 10‐20 times daily, even with four antiseizure medicines. For the treatment of hand dyskinesia, she underwent left pallidothalamic tractotomy and her right‐hand dyskinesia significantly improved. Fourteen months later, she had experienced no focal impaired awareness seizure and the aura decreased to one to three times per month. The second case was that of a 15‐year‐old boy diagnosed with progressive myoclonic epilepsy, who developed generalized tonic‐clonic seizure, which manifested once every month, despite treatment with five antiseizure medicines. After surgery, myoclonic movements in his right hand slightly improved. A one‐year follow‐up revealed that he had not experienced a generalized tonic‐clonic seizure. The lesion locations in the two cases were close to the vicinity of Jinnai's Forel‐H‐tomy. Forel's field H deserves reconsideration as a treatment target for intractable epilepsy.